Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41390-018-0263-x
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse optical tomography for the detection of perinatal stroke at the cot side: a pilot study

Abstract: BackgroundPerinatal stroke is a potentially debilitating injury, often under-diagnosed in the neonatal period. We conducted a pilot study investigating the role of the portable, non-invasive brain monitoring technique, diffuse optical tomography (DOT), as an early detection tool for infants with perinatal stroke.MethodsFour stroke-affected infants were scanned with a DOT system within the first 3 days of life and compared to four healthy control subjects. Spectral power, correlation, and phase lag between inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…However, bilateral visual cortex connectivity was absent in the preterm infant with left occipital hemorrhagic stroke 26 . Similarly, researchers have recently demonstrated reduced interhemispheric connectivity in four infants following perinatal stroke as compared to four healthy infants 220 …”
Section: Dot Applications In Human Clinical Populationsmentioning
confidence: 95%
“…However, bilateral visual cortex connectivity was absent in the preterm infant with left occipital hemorrhagic stroke 26 . Similarly, researchers have recently demonstrated reduced interhemispheric connectivity in four infants following perinatal stroke as compared to four healthy infants 220 …”
Section: Dot Applications In Human Clinical Populationsmentioning
confidence: 95%
“…Such a concept, in fact, has already been explored in DOT for the deep-brain studies in new-born babies. 200,209 Considering all the extra quality checks that will need to be fulfilled for the use in new-born, if luminescence-based nanotechnology follows a similar path, then the development of the materials should start focusing on these quality checks at the level of material design.…”
Section: Pathways To Address the "Tissue Attenuation" Issuementioning
confidence: 99%
“…Due to the reduced dimensions of their tissues, the number of organs considered viable as indicated in Table would increase, potentially giving rise to more possibilities for the detection and treatment of diseases. Such a concept, in fact, has already been explored in DOT for deep-brain studies in newborn babies. , Considering all the extra quality checks that will need to be fulfilled for use in newborns, if luminescence-based nanotechnology follows a similar path, then the development of the materials should start focusing on these quality checks at the level of material design. If, however, the intention is still to keep the applicability of luminescent NPs as broad as possible (including adults), then the use of endoscopic techniques will have to be considered.…”
Section: Characteristics Of a Nanoparticle-based Fluorescence Imaging...mentioning
confidence: 99%
“…EEG-fNIRS systems are of particular interest in neonatal brain research since both methods are minimally invasive, silent, and can be employed cot-side [23]. Infant studies have demonstrated that EEG-fNIRS is particularly important for understanding the development of neurovascular coupling and its (dys)regulation in association with neuropathology [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%